Concept of street light control system using the plc technology - Skoczylas, M.; Szydelko, W. (Видавництво Національного університету "Львівська політехніка", 2004)
The lights in the streets, roads and squares is a big budget load, so the solutions for decreasing of the costs are strongly required. The paper includes two proposition of dealing with the problem. The first is finding more efficient sources of light and the second is optimizing the usage of existing ones. The second way has been described in this work.